I survived the Children's Blizzard, 1888 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic Inc., 2018)
When John Hale's parents moved from Chicago to a farm in the Dakota Territory in the late 1880s, he was not happy (too hot in summer, too cold in winter, and that is just the beginning); but after a year, and now eleven, he has settled in and made some friends at school--but when a sunny day in January 1888 turns abruptly into a deadly blizzard he will need all his strength and courage to survive what became known to history as The Children's Blizzard.
Includes bibliographical references.
Keywords: Blizzards -- Dakota Territory -- History -- 19th century -- Juvenile fiction; Pioneer children -- Dakota Territory -- Juvenile fiction; Survival -- Dakota Territory -- Juvenile fiction; Blizzards -- Fiction; Frontier and pioneer life -- Dakota Territory -- Fiction; Survival -- Fiction; Dakota Territory -- History -- Juvenile fiction; Dakota Territory -- Fiction